Optimalisasi Penggunaan Drone dalam Operasi Penyelamatan di Perairan: Meningkatkan Efisiensi dan Keselamatan dalam Situasi Darurat - Supri S; Wahyudono W; Alwazir Abdusshomad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The use of drones in water rescue operations offers an innovative solution to enhance efficiency and safety in emergency situations. Challenges such as limited accessibility, unpredictable weather conditions, and high risks for rescue teams can be addressed with drone technology equipped with advanced sensors, including thermal and infrared cameras. This study aims to examine the optimization of drone utilization in water rescue operations. A literature review method was employed by analyzing relevant academic sources. The findings indicate that drones can accelerate victim searches, improve detection accuracy, and assist in the distribution of rescue equipment. However, several challenges remain, including battery life limitations, extreme weather conditions, and regulatory constraints that require further adjustments. With continued technological advancements and supportive policies, drones have the potential to become essential tools in enhancing the effectiveness of water rescue operations.